Structural Model of Life Satisfaction Based on Emotional Regulation, Problem-Solving Skills, and Tolerance of Ambiguity Mediated by Personality Traits of Couples - kazemzadeh , Mohammad; Asadzadeh , Hassan; Moazedian , Ameneh; Karami, Abolfazl (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to develop a structural model of life satisfaction based on emotional regulation, problem-solving skills, and tolerance of ambiguity (TA) mediated by personality traits of couples. Methods: The research method was descriptive-correlational, and the statistical population consisted of all couples who visited counseling centers 2 and 5 in Tehran in 2018. Among them, 380 individuals were selected by convenience sampling. The life satisfaction questionnaire by Diner et al. (1985), cognitive emotion regulation questionnaire by Garnfsky et al. (2001), Hepner''s problem-solving questionnaire (1982), tolerance of ambiguity questionnaire by McLain (1993), and the five-factor NEO personality inventory (NEO-PI) by McCrae and Costa (1985) were used to collect data. Data were analyzed using structural equations, SPSS22, and AMOS24. Results: The results indicated a direct significant effects of emotional regulation (P=0.01, β=0.40), problem-solving skills (P=0.01, β=0.32), Tolerance of ambiguity (P=0.01, β=0.22), and personality traits- neuroticism (P=0.01, β=0.22), extraversion (P=0.01, β=0.23), openness to experience (P=0.01, β=0.19), agreeableness (P=0.01, β=0.22), and conscientiousness (P=0.01, β=0.27) on life satisfaction. There was also a significant relationship between emotional regulation, problem-solving skills, and tolerance of ambiguity with life satisfaction mediated by personality traits (P=0.01). Conclusion: Personality traits play a mediating role in the relationship between emotional regulation, problem-solving skills, and increasing tolerance of ambiguity. Life satisfaction can increase by teaching problem-solving skills and emotional regulation.